Visual Position and Juxtaposition: An Analytical Study of Liberty Leading the People and Moon-Woman Cuts the Circle - Chaulagain, Yashoda (Tribhuvan University Journal, 2018)
This paper explores the idea of romantic and modern painting with the reference of Delacroix’s painting “Liberty Leading the People” and Jackson Pollock’s painting “Moon Woman Cuts the Circle”. Both painters representing different era, portray different styles, background, color, tempo, and textures in their painting. Delacroix’s painting expresses inner emotions and realistic world. His painting is emotional, it seems to be natural and exotic. He has used arches, sculptures, and gray color dominantly. In contrast to Delacroix, Pollock’s painting is experimental. It has abstraction and two-dimensionality. It looks rational that represents the frustrated and chaotic world in abstract form. In this sense, Delacroix’s painting “Liberty Leading the People” represents the liberty, equality, and fraternity. A woman personifying the concept and the goddess of liberty leads the people forward over the bodies of the fallen men holding the flag of the French Revolution. On the other hand, Jackson Pollock’s painting “Moon Woman Cuts the Circle” reflects the modern world representing woman the symbol of peace, color tempo suggests the domination of violence and bloodshed. The weapon shows the domination of the power which is violent. Delacroix’s painting suggests the hope of change and bright future but Pollock seems to be pessimistic in his painting.